Perancangan Sistem Informasi Absensi Akuntansi STAIN Bengkalis Berbasis Android: PERANCANGAN SISTEM INFORMASI ABSENSI AKUNTANSI STAIN BENGKALIS BERBASIS ANDROID - Jamilah, Titin Trisnawati; Jamilah, Jamilah; Rahmayanti, Mentari Tri Indah (LPPM Universitas Pahlawan Tuanku Tambusai, 2023)
Student attendance aims to monitor the level of student attendance and discipline students. Recording student attendance which is currently done manually on paper can be improved, so as to improve the quality of attendance data processing, service quality and systems in the STAIN Bengkalis Accounting study program. This research aims to develop an Android-based STAIN Bengkalis accounting attendance information design that can be used on lecturers' and students' mobile devices. SDLC is the method used to develop the design of Android-based STAIN Bengkalis accounting attendance information in this research. The Android-based STAIN Bengkalis accounting attendance information design can facilitate lecturers and students in carrying out the daily attendance process.